1970
DOI: 10.5713/ajas.2013.13097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hybridization on Carcass Traits and Meat Quality of Erlang Mountainous Chickens

Abstract: Native chickens hold a significant share of the market in China. In response to the huge demand from the market, the productivity of Chinese native chickens needs to be improved. Cross breeding is an effective method to increase productivity, although it might affect meat quality. In this study, two pure lines (SD02 and SD03) of Erlang mountainous chickens were hybridized with a yellow feather and faster growing line (SD01). The effect of hybridization on carcass and meat quality (physiochemical and textural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
4
16
5
Order By: Relevance
“…These changes mainly relate to color, fat cover, muscle fiber thickness, tenderness, chemical and sensory characteristics of the meat and depend on the genotype of the birds, their rearing methods, feeding and slaughter age. As Yin et al (2013) indicated, later maturing birds are predisposed to breeding in extensive conditions, with a good rate of weight gain, therefore a way to improve the growth and muscularity of birds is to crossbreed different breeds of hens, which was also used in our own research. The obtained hybrids -the capons were distinguished by a significantly higher body weight compared to pure-bred hens, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These changes mainly relate to color, fat cover, muscle fiber thickness, tenderness, chemical and sensory characteristics of the meat and depend on the genotype of the birds, their rearing methods, feeding and slaughter age. As Yin et al (2013) indicated, later maturing birds are predisposed to breeding in extensive conditions, with a good rate of weight gain, therefore a way to improve the growth and muscularity of birds is to crossbreed different breeds of hens, which was also used in our own research. The obtained hybrids -the capons were distinguished by a significantly higher body weight compared to pure-bred hens, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies found great variations in IMP content, both within and among species. IMP content from various studies in chickens ranged from 1.40 to 1.81 mg/g [19,20]. A few studies available in ducks also showed large variations in IMP content.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…In this sense, the greater ether extract content may also be associated with the elevated nutrient intake. Yin et al [45] reported that the composition and content of amino acids are critical evaluation indices, which are associated with the flavor and nutritional value of meat. Our results showed that the meat of Tibetan sheep was rich in a variety of essential and nonessential amino acids like other livestock (e.g., Hu sheep, the Hengshan goat, and Yanbian cattle) distributed in the low-altitude areas of China [46][47][48].…”
Section: Meat Compositionmentioning
confidence: 99%